(untitled) (VITAE Academia Biomédica Digital, 2025)
SARS-CoV-2, the cause of the COVID-19 pandemic has significantly impacted cardiovascular healthcare. Patients with pre-existing cardiovascular disease are at higher risk of morbidity and mortality. The virus may affect the heart directly and indirectly with clinical syndromes of acute myocardial injury, myocarditis, acute coronary syndromes, heart failure, arrhythmias, and venous thromboembolism. Some therapeutics under investigation for COVID-19 may also have adverse cardiac effects. The involvement of the RAAS system in viral entry makes it pertinent to consider the effects of medications that modulate the system. Comprehensive knowledge of peculiar cardiovascular manifestations of COVID-19 and the role of RAAS in the prognosis of COVID-19 disease is needed for optimal patient management.